2021
DOI: 10.3390/ijms22052576
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SGLT-2 Inhibition on Cardiometabolic Abnormalities in a Rat Model of Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in reproductive-age women. PCOS is characterized by hyperandrogenism and ovulatory dysfunction. Women with PCOS have a high prevalence of obesity, insulin resistance (IR), increased blood pressure (BP), and activation of the renin angiotensin system (RAS). Effective evidence-based therapeutics to ameliorate the cardiometabolic complications in PCOS are lacking. The sodium-glucose cotransporter-2 (SGLT2) inhibitor Empagliflozin (EMPA) reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 63 publications
5
40
1
Order By: Relevance
“…Although is clear that obesity exacerbates the cardiometabolic complications in PCOS women [4], the mechanism by which hyperandrogenemia promotes white adipocytes (WAT) expansion remains unclear. We previously demonstrated that hyperandrogenemia in female rats recapitulates several of the cardiometabolic features observed in women with PCOS, including increased body weight, BMI, fat mass, IR, blood pressure, and albuminuria [13,14]. The expansion of WAT is present in both the subcutaneous (SAT) and visceral WAT (VAT) [13,15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Although is clear that obesity exacerbates the cardiometabolic complications in PCOS women [4], the mechanism by which hyperandrogenemia promotes white adipocytes (WAT) expansion remains unclear. We previously demonstrated that hyperandrogenemia in female rats recapitulates several of the cardiometabolic features observed in women with PCOS, including increased body weight, BMI, fat mass, IR, blood pressure, and albuminuria [13,14]. The expansion of WAT is present in both the subcutaneous (SAT) and visceral WAT (VAT) [13,15,16].…”
Section: Introductionmentioning
confidence: 96%
“…They potentially reduce plasma glucose levels by blocking glucose reabsorption in the renal proximal tubule of patients with diabetes 17–19. SGLT-2 inhibition has also shown positive effects on reducing body weight, blood pressure, cardiovascular and renal complications, attenuating beta-cells exhaustion and relieving oxidative damage and inflammation 20–23…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several reports have investigated the use of SGLT-2 inhibitors for PCOS, such as empagliflozin, licogliflozin and dapagliflozin 20 24–27. In PCOS mouse models displaying hyperandrogenism, empagliflozin was found to be beneficial in reducing blood pressure and the amount of fat 20.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations